Analisis Wacana Rekonstruksi Sejarah 1998 pada Film Pengepungan di Bukit Duri - Prasanti Ayuningtyas Prawirohardjo; Triyono Lukmantoro (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the discourse of historical reconstruction of the 1998 tragedy depicted in the film